The looking glass war. - Le Carré, John, 1931- (New York, Coward-McCann, 1965)
Focuses on a former military espionage department in London and its attempts to train an agent for a mission in East Germany.
Keywords: Intelligence service -- Great Britain -- Fiction; Spy stories